Cannabidiol administration into the bed nucleus of the stria terminalis alters cardiovascular responses induced by acute restraint stress through 5-HT1A receptor - Gomes, Felipe V.; Alves, Fernando H.F.; Guimarães, Francisco S.; Correa, Fernando M.A.; Resstel, Leonardo B.M.; Crestani, Carlos Cesar [UNESP] (My University, 2013)
Systemic administration of cannabidiol (CBD) is able to attenuate cardiovascular responses to acute restraint stress through activation of 5-HT1A receptors. Previous results from our group suggest that the bed nucleus of the stria terminalis (BNST) is involved in the antiaversive effects of the CBD. Moreover, it has been proposed that synapses within the BNST influence restraint-evoked cardiovascular changes, in particular by an inhibitory influence on the tachycardiac response associated to restraint stress. Thus, the present work investigated the effects of CBD injected into the BNST on cardiovascular changes induced by acute restraint stress and if these effects would involve the local activation of 5-HT1A receptors. The exposition to restraint stress increased both blood pressure and heart rate (HR). The microinjection of CBD (30 and 60nmol) into the BNST enhanced the restraint-evoked HR increase, in a dose-dependent manner, without affecting the pressor response. The selective 5-HT1A receptor antagonist WAY100635 by itself did not change the cardiovascular responses to restraint stress, but blocked the effects of CBD. These results showed that CBD microinjected into the BNST enhanced the HR increase associated with acute restraint stress without affecting the blood pressure response. Although these results are not in agreement with those observed after systemic administration of CBD, they are similar to effects observed after reversible inactivation of the BNST. Moreover, similar to the effects observed after systemic administration, CBD effects in the BNST seem to depend on activation of 5-HT1A receptors. © 2012 Elsevier B.V. and ECNP.
Keywords: Arterial pressure; Aversive situation and serotonin receptors; Cannabinoids; Extended amygdala; Heart rate; antibiotic agent; bromethol; cannabidiol; flunixin meglumine; n [2 [4 (2 methoxyphenyl) 1 piperazinyl]ethyl] n (2 pyridyl)cyclohexanecarboxamide; pentabiotico; serotonin 1A antagonist; serotonin 1A receptor; unclassified drug; amygdaloid nucleus; animal experiment; animal model; arterial pressure; blood pressure; cardiovascular response; controlled study; drug effect; heart rate; immobilization stress; male; microinjection; nonhuman; pressor response; priority journal; rat; stria terminalis